Judge's Consideration of Evidence in the Crime of Illegal Access - Firdaus; Bisma Putra Pratama (Master of Law Program, Ekasakti University, 2025)
The approach used is the Normative Juridical approach. The data used is secondary data collected through literature studies. The proof by the judge of the crime of illegal access in Decision Number 62/Pid.Sus/2020/PN Pti and Decision Number 10/Pid.Sus/2021/PN Pli is by means of evidence and corroborated by the judge's conviction through a criminal justice process. To determine that a criminal act has occurred, law enforcement officials must prove that the suspect has met the criminal elements suspected or charged. The evidence used is electronic documents and electronic information. The electronic documents in decision number 62/Pid.Sus/2020/PN Pti are print out data systems in the form of IMEI and MAC Address, printout transaction data and transaction data by the Shoppe seller account (seller) while in decision number 10/Pid.Sus/2021/PN Pli is 1 (one) bundle of printed credit delivery transaction reports through the Digipos application and 1 (one) sheet of screenshot prints of the DigiPos account. Application of Criminal Procedure by Judge where the defendant has been legally and convincingly proven guilty of committing a criminal act